CHANGING THE LEGAL WORLD – ARTIFICIAL INTELLIGENCE AND COMMERCIAL INTERMEDIARY CONTRACTS - Belović, Jelena M; Spalević, Žaklina; Jakšić, Jelena (Pravo, teorija i praksa, 2025)
Common law is one of the oldest forms of legal regulations that developed through unwritten rules and norms of behaviour that were established in the earliest communities. This law was based on customs adopted by the members of social community and passed down from generation to generation. In the absence of codified laws, customs made it possible to maintain social order and resolve conflicts within the community. One of the most well-known norms of common law was the institute of blood vengeance. It represented a way of maintaining balance and it could be said to embody ‘justice’ within the community, reflected in the practice where murder or injury was reciprocated with the same measure towards the perpetrator or his family. In the earliest periods, this rule was deeply rooted in the belief that only revenge could restore lost honor and establish balance within the community. Given the importance of the institute of blood vengeance, this paper will analyze when and in which documents blood vengeance was first mentioned, its characteristics, as well as its two institutions – oath and conciliation. These institutions, by their origin and purpose, can be said to oppose this custom, and within them, certain elements for its suppression can be found.Artificial intelligence poses a challenge to modern legal systems, as it represents a societal phenomenon and an extension of social reality. Aware that social reality is rapidly evolving due to technological progress, we rightfully question whether the existing legal frameworks are sufficient and adequate to accommodate the changes occurring in the field of artificial intelligence. Specifically, legal subjects include natural persons and legal entities. Can we still limit ourselves to only these two categories today, when computers equipped with cutting-edge artificial intelligence programs increasingly play a significant role in making decisions with legal consequences? This paper will focus on analyzing contemporary social trends and their impact on the existing legal framework, utilizing an evolutionary interpretation of legal institutes. Through the example of natural and legal persons acting as intermediaries in the provision of services, specifically in transportation, we will examine this phenomenon and potential future developments. In this context, the paper will focus on judicial practice related to the Uber case.